Pirólise de resíduos de embalagens cartonadas e seus componentes puros : uma avaliação cinética - Alvarenga, Larissa Machado (2013)
Many processes have been used for recycling of carton packaging wastes. The pyrolysis highlights as a promising technology to be used for recovering the aluminum from polyethylene and generating products with high heating value. In this research, a study on pyrolysis reactions of carton packaging wastes and its pure components was performed in order to estimate the kinetic parameters of these reactions. For this, dynamic and isothermal thermogravimetric analyses were carried out and two different kinds of kinetic models were used: the isoconversional and Independent Parallel Reactions (IPR). Isoconversional models allowed to calculate the overall activation energy of the material pyrolysis reaction, in according to their conversions. The activation energy values obtained with Ozawa, KAS and Starink models for carton packaging pyrolysis were similar (168.30, 166.54 and 166.78 kJ.mol-1), as well as the results found for polyethylene (137.41, 132.49, 132.98 kJ.mol-1) and cardboard (155.66, 153.46, 153.69 kJ.mol-1). Nevertheless, the Kissinger method the method of Kissinger estimated lower values of activation energy for carton packaging (121.42 kJ.mol-1) and cardboard (144.89 kJ.mol-1), and a higher value for polyethylene activation energy (155.15 kJ.mol-1). The IPR model, in turn, allowed the calculation of kinetic parameters of each one of the carton packaging and paperboard subcomponents. The estimated values for the kinetic parameters of the material subcomponents were within the range of values found in the literature. The mass loss of materials simulated with the RPI model showed a good fit to the experimental data obtained by thermogravimetry, presenting deviation values in the same order of magnitude as those found in other literature studies. It was also performed a parametric sensitivity analysis of IPR model, that shown that the activation energy affected the total conversion of the material more strongly than the pre-exponential factor. In general, this work contributed to the quality evaluation of the kinetic models adjustment and for the calculation of the kinetic parameters of material pyrolysis.